An Overview on Security Schemes Based on Elliptic Curve for Cloud-Iot - Ayoub, Amrani; Najat, Rafalia; Abouchabaka, Jaafar (JOURNAL OF ADVANCES IN NATURAL SCIENCES, 2018)
The Internet of things appears as a solution in order to connect people around the world. With this concept of interconnection, sharing and dissemination of information between different physical objects. Many objects and services in different fields will be created, such as smart homes, e-health, transport and logistics that will make our everyday needs easier. The main characteristic of a connected object is that it must be identifiable, using technologies such as RFID (Radio-Frequency Identification), must interact with the environment by adding sensory techniques, and finally a connected object must be able to communicate with others. The evolution of Internet of things, increase the number of connected objects. Devices with sensors, generate a huge number of data. With this evolution, the big questions come! how can we control this big data? Cloud Computing a notion that is not newer than the IoT concept, but it's a revolution has steadily been gaining ground. It's a technology that offers to end users a great services in terms of storage, elasticity, analyzing data and other services . In this paper, we cite the benefits of integrating Cloud Computing and Internet of things to manage data provided by physical object and security difficulties that may have this convergence. We also present an overview of the security algorithms proposed in the literature, based on elliptic curves, in order to secure communication between smart objects and cloud computing.